EPIDEMIC OF RIFT VALLEY FEVER IN SUDAN, GEZIRA, 2007; GEZIRA EXPERIENCE - El Imam, Mohamed; Abdelkareem, Abdullah; Yosif, Nasreldeen; Elsabiq, Mohamed; Elhasan, Elhasan M.; Mohamadani, A.A.; Ahmed, Badreldeen; Miskeen, Elhadi; Khalafallah, Osman (مجلة الجزيرة للعلوم الصحية; مجلد 5 عدد 2 (2009), 2009)
In the last 3 months of 2007, an acute episode of an ill-defined severe febrile illness presented to Medani hospital isolation words, with severe hemorrhagic manifestations. This initially did not harbor any attention as other possibilities were thought of like severe malaria , septicaemia but by the end of the same week the number of patients increased dramatically and the suspicion was put and the whole case was addressed officially in an epidemical paradigm. This study was conducted in Wad Medani Teaching Hospital. From the beginning of 41st week of the year 2007, the Gezira state in Sudan was tremendously affected by an epidemic of Rift valley fever as declared by the WHO authorities (11).all the districts of the estate were involved with a total number of patients was around 392. During the period of epidemic of RVF, (week 41.2007 - up to the 1st week of January 2008) total number of patients admitted were about 392 and total number of patients died were 158 patients .The main presenting symptoms were fever, epistaxsis, haematemesis and vaginal bleeding, and the main complication was acute renal failure and death.